Implementasi Pendidikan Karakter Dalam Ekstrakurikuler Drumben di Sekolah Dasar Negeri Kebon Besar 1 Kota Tangerang: Penelitian - Lily Septiani; Salsabila Mulyadih; Rahmawati Eka Saputri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Character education should start at an early age, especially in elementary school. Introducing the concept of character education at an early stage is very important to develop a child's personality as a whole. One method that can be used to instill character values ​​is through extracurricular activities. Drumben extracurricular activities in schools serve as an effective means to teach values ​​such as discipline, responsibility, cooperation, and self-confidence. This study aims to investigate how character education is implemented in drumben extracurricular activities at Kebon Besar 1 Elementary School. This study uses a qualitative method with a descriptive approach, which aims to provide an in-depth picture. Data were obtained through observation, interviews, and documentation. The results of the study indicate that drumben activities are successful in forming discipline, responsibility, confidence, and cooperation among students, although there are several challenges that must be faced.